Application of Ligation of Internal Iliac Artery and Uterine Artery in Pernicious Placenta Previa - Lijuan Bai; Jie Lin; Qiuni Shen; Xiaodong Fu (IMR Press, 2023)
Backgrounds: To investigate the use of vascular ligation in the treatment of pernicious placenta previa. Methods: Clinical data from 199 patients with pernicious placenta previa were collected and divided into groups according to placenta location, placenta accretion and vessel ligation, the pregnancy outcome of each group was compared. Results: The unplanned reoperation rate was lower for the internal iliac artery ligation group than the group without internal iliac artery ligation (p < 0.05). The intraoperative bleeding volume, blood transfusion volume, and intensive care unit (ICU) admission rate were lower for the prophylactic internal iliac artery ligation group than the therapeutic ligation group (p < 0.05), and in the hysterectomy patients, intraoperative bleeding was lower in the prophylactic internal iliac artery ligation group than the therapeutic ligation group (p < 0.05). The hysterectomy rate was lower for the uterine artery ligation group than the group without uterine artery ligation (p < 0.05); and for superficial and deep placental accreta, the operation time of uterine artery ligation group was shorter than internal iliac artery ligation group, intraoperative bleeding volume, blood transfusion volume, and ICU admission rate have no significant difference, when placental penetrating implantation was performed, patients with internal iliac artery ligation were statistically more severely ill, but there was no difference in prognosis. Conclusions: Vascular ligation is an effective means of managing high-risk obstetric bleeding and helps to avoid hysterectomy and unplanned reoperation, but surgeons need to choose the appropriate ligation method to improve patient prognosis, considering the patient's condition and his or her skills.